Developing a policy brief on physical activity promotion for children and adolescents - Messing, Sven; Gelius, Peter; Abu-Omar, Karim; Marzi, Isabel; Beck, Franziska; Geidl, Wolfgang; Grüne, Eva; Tcymbal, Antonina; Reimers, Anne Kerstin; Pfeifer, Klaus (Frontiers in Public Health, 2023)
Introduction While there are several approaches to collect basic information on physical activity (PA) promotion policies, some governments require more in-depth overviews on the situation in their country. In Germany, the Federal Ministry of Health expressed its interest in collecting detailed data on target group specific PA promotion, as relevant competences are distributed across a wide range of political levels and sectors. This study describes the development of a policy brief on physical activity promotion for children and adolescents in Germany. In particular, it addresses two major gaps in the current literature by systematically assessing good practice examples and “routine practices,” i.e., PA promotion activities already taking place on large scale and regular basis. Materials and methods Based on relevant national and international guidelines, the TARGET:PA tool was co-produced by researchers and ministry officials. It includes (1) PA recommendations, (2) national prevalence rates, (3) recommendations for PA promotion, and data on national (4) routine practices, (5) good practice projects and (6) policies. Data were collected for children and adolescents in Germany using desk research, semi-structured interviews and secondary data analysis. Results A policy brief and scientific background document were developed. Results showed that 46% of the 4–5-year-olds fulfil WHO recommendations but only 15% of the 11–17-year-olds, and that girls are less active than boys. Currently, in Germany no valid data are available on the PA behaviour of children under the age of three. An overview of routine practices for PA promotion for children and adolescents was compiled, and experts were asked to critically assess their effectiveness, reach and durability. Overall, 339 target group specific projects for PA promotion were found, with 22 classified as examples of good practice. National PA policies for children and adolescents were identified across different sectors and settings. Conclusion The study provides a comprehensive overview of the current status of PA promotion for children and adolescents in Germany. The co-production of the policy brief was a strength of the study, as it allowed researchers to take the needs of ministry officials into account, and as it supported the immediate uptake of results in the policymaking process. Future studies should test the applicability of the TARGET:PA tool to different target groups and countries.